S Model Pengentasan Kemiskinan dengan Multidimenstional Poversty Index Bagi Eks-Pekerja Migran Indonesia Wanita di Jawa Timur - Sayekti Suindyah Dwiningwarni; Sri Juni Woro Astuti; Suyanto Suyanto; Syamsiyah Yuli Dwi Andari (Institut Teknologi dan Sains Mandala, 2025)
Data on ex-Indonesian Migrant Workers (PMI) is unavailable at the central, regional, and regional levels. This is because ex-PMIs never report their whereabouts if they are no longer working abroad, nor do village officials ever collect data on former -PMIs. This differed from PMI's conditions when it became PMI, a foreign exchange supplier for countries, regions, and regions. This research aims to (1) map the condition of ex-PMI women from employment, economic, and social data; (2) formulate a model for alleviating poverty for ex-PMI women. The method used is a survey method and a quantitative approach. This research was conducted in TulungAgung district, with 300 respondents. The data analysis method used is quantitative descriptive. Research results (1) survey results: (a) in the villages of Besole, Besuki, and TanggulTurus, data was found that there were approximately 474 female ex-PMIs, (b) 65.6% of female ex-PMIs had no income, (c) 32.4% ex-PMI Women do not work. (2) MPI calculation results show that Besuki and TanggulTurus villages produce the lowest MPI value, 0.033, while Besole village produces the lowest MPI value, 0.066. This shows that Besuki, TanggulTurus, and Besole villages are in the very low poverty classification.